1993
DOI: 10.2135/cropsci1993.0011183x003300010015x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the fan Allele and Agronomic Traits in Soybean

Abstract: Normal levels of linolenic acid (70‐80 g kg‐1) in soybean [Glycine max (L.) Merr.] oil adversely affect oil flavor and stability. The mutation‐induced line C1640 has half the normal level of linolenic acid (37 g kg‐1), but is 24% lower yielding than ‘Century’, from which it was selected. This study was conducted to determine if there are genetic relationships betweena gronomictr aits and the fan allele for low linolenic acid identified in C1640. Century and ‘Harper’, both with the FanFan alleles for normal 18:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 12 publications
3
15
0
Order By: Relevance
“…This means, that under usual growing conditions the lower C18:3 content in the cytoplasmic membranes of roots and leaves seems to be tolerated without yield losses. Similar results were demonstrated in mutant lines of soybean (Wilcox et al 1993) with decreased C18:3 content in seed oil and root lipids (Wang et al 1989); no association was found between C18:3 content and characters such as seed yield, maturity, lodging or plant height in F2-derived lines of the two cross combinations investigated.…”
Section: Discussionsupporting
confidence: 75%
“…This means, that under usual growing conditions the lower C18:3 content in the cytoplasmic membranes of roots and leaves seems to be tolerated without yield losses. Similar results were demonstrated in mutant lines of soybean (Wilcox et al 1993) with decreased C18:3 content in seed oil and root lipids (Wang et al 1989); no association was found between C18:3 content and characters such as seed yield, maturity, lodging or plant height in F2-derived lines of the two cross combinations investigated.…”
Section: Discussionsupporting
confidence: 75%
“…Oleic acid and linolenic acid contents were demonstrated to be influenced greatly by temperature and modifier genes in several studies (Chapman et al 1976;Dornbos and Mullen 1992;Graef et al 1988;Hyten et al 2004;Wilcox et al 1993). It is shown clearly in this study that when two mutant FAD3A and FAD3C genes were incorporated into a high oleic acid background to reduce the enzymatic activity of FAD3, the linolenic acid content of HOLL soybeans was still affected by environmental factors while the oleic acid content showed a reduction in the Columbia, MO location compared to Portageville, MO that was statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that reduction of linolenate content in soybean oil did not affect yield, maturity, and lodging. Wilcox et al (1993) determined the genetic associations of the mutant allele in C1640 that controls reduced linolenate content with agronomic traits. They reported that the allele for reduced linolenate had no genetic relationships with agronomic characters.…”
Section: Literature Reviewmentioning
confidence: 99%